Estimación del estrés laboral en la unidad de cuidados críticos en un hospital de guayaquil - Sudario López, Jaime Andrés (2025)
Work stress in critical care units (CCU) in hospitals in Ecuador is an important issue to reevaluate every year, the pressure of extreme responsibility, constant attention and quick decisions can have serious consequences on the health of professionals, so this study aims to assess the level of stress during the work performance of nurses in a hospital in the city of Guayaquil, For this purpose, a study modality based on the quantitative approach was used, being the instrument used the questionnaire based on the Perceived Stress Scale Test (PSS) for its acronym in English, The main findings were that 65% of the respondents had a high level of stress, which indicates that a large majority of them have high levels of stress in their work environment, which represents a risk for the health of both the professionals and their patients. On the other hand, 20% report a moderate level of stress, which indicates that they can handle stress; however, this group is still at risk of developing high stress if working conditions do not improve or if work demands increase, concluding that lifestyle is also a factor that plays an important role in the development or reduction of stress levels so it is necessary to promote self-care habits such as physical activity, a balanced diet and relaxation strategies.